2013
DOI: 10.1172/jci61110
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular NEDD4-2 deficiency causes NCC-mediated salt-dependent hypertension

Abstract: The E3 ubiquitin ligase NEDD4-2 (encoded by the Nedd4L gene) regulates the amiloride-sensitive epithelial Na + channel (ENaC/SCNN1) to mediate Na + homeostasis. Mutations in the human β/γENaC subunits that block NEDD4-2 binding or constitutive ablation of exons 6-8 of Nedd4L in mice both result in salt-sensitive hypertension and elevated ENaC activity (Liddle syndrome). To determine the role of renal tubular NEDD4-2 in adult mice, we generated tetracycline-inducible, nephron-specific Nedd4L KO mice. Under stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(176 citation statements)
references
References 56 publications
14
162
0
Order By: Relevance
“…The increased Na + reabsorption by NCC would decrease Na + delivery to ENaC, thus impairing the electrochemical gradient required for K + secretion by ROMK and H + by the vacuolar H + -ATPase. Other mouse models with increased NCC activity do not, however, display hyperkalemia or metabolic acidosis (18,26,27). In addition, we found that ENaC activity is conserved in WNK1 +/FHHt animals.…”
Section: Discussionmentioning
confidence: 59%
“…The increased Na + reabsorption by NCC would decrease Na + delivery to ENaC, thus impairing the electrochemical gradient required for K + secretion by ROMK and H + by the vacuolar H + -ATPase. Other mouse models with increased NCC activity do not, however, display hyperkalemia or metabolic acidosis (18,26,27). In addition, we found that ENaC activity is conserved in WNK1 +/FHHt animals.…”
Section: Discussionmentioning
confidence: 59%
“…Recent data indicate that Nedd4-2 is yet another player in the pathway by which aldosterone activates NCC (Figure 3) [2,99]. Nedd4-2 was shown to stimulate ubiquitylation of NCC and decreased its activity and surface expression in vitro and in vivo, while SGK1 prevented these effects [2].…”
Section: Ubiquitin Ligasesmentioning
confidence: 99%
“…This NCC signaling cascade consists of a multikinase network which includes the kinases WNK, SPAK, OSR1, and SGK1 [130]. More recently, proteins involved in ubiquitylation including Nedd4-2, Kelch-like 3, and Cullin 3 were also found to regulate NCC [2,7,68,99]. Many of these regulatory proteins were identified because mutations in their genes result in familial hyperkalemic hypertension (FHHt, also called pseudohypoaldosteronism type II or Gordon syndrome, see also "Relation to diseases" below).…”
Section: Kinasesmentioning
confidence: 99%
See 2 more Smart Citations